Ghuru Tolang: Shift in Patterns of Santri-Kiai Socio-Cultural Relations in the Life of the Madurese Millennial Society - Thoha, Mohammad; Fathorrozy; Zaiful Rosyid, Moh.; Abrori, Miftahul; Tianah, Itaanis (IAIN Madura, 2024)
The goal of this study is to uncover the millennial generation's perception of ghuru tolang as well as the pattern of socio-cultural relations established by the Madurese millennial community. This research employs a qualitative-phenomenological approach, with data gathered through interviews, observation, and documentation. The information was analysed in three stages: reduction, display, and verification. According to the findings of this study, the figure and role of ghuru tolang are essentially the same in the eyes of the millennial generation, despite a slight shift. According to him, ghuru tolang is a religious educator and founder who must be respected and obeyed. Ghuru tolang, on the other hand, does not stand out from other teachers in their eyes.so there is no sacredness that must be overly addressed. Nevertheless, the millennial generation still positions ghuru tolang as a religious and social leader so that he is considered a cultural symbol that fully adheres to traditional religious values and has important meaning for the Madurese people. The social relations that are built between the ghuru tolang and the millennial generation are imbued with a strong spiritual aspect where there is a special relationship, namely a relationship that is imbued with the spirit of Nasyr al 'ilmi. The closeness of the relationship between the two is also based on a strong emotional closeness like the psychological relationship between parents and their children.